Wpływ kursu walutowego na wielkość eksportu polskich produktów mleczarskich - Wierzejski, Tomasz (The Effects of the Exchange Rate on the Volume of Exports of Polish Dairy Products, 2006)
Exchange rate is one of the key factors determining the decision whether or not a given enterprise should enter foreign markets. The aim of the present study is to determine the effects of the Polish zloty to euro exchange rate on the volume of exports of particular dairy products following the accession of Poland to the European Union. Over the analyzed period the exchange rate of Polish zloty strengthened against euro, and an increase in export sale was observed in the dairy sector. The coefficients of correlation calculated in the study and statistical tests reveal that the exchange rate of euro had a slight effect on the export volume in the dairy industry. On the other hand, the strengthening of the exchange rate of Polish zloty was reflected by worse financial results of exporting enterprises, especially those that sell their products on foreign markets. It seems that the lower and lower euro to Polish zloty exchange rate recorded in 2005 will cause a decrease in the volume of exports as soon as in 2006.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 481-487